Macrophage metallothioneins participate in the antileishmanial activity of antimonials - Vargas, Deninson Alejandro; Gregory, David J; Roni Nitzan Koren; Zilberstein, Dan; Ashton Trey Belew; El-Sayed, Najib M; Gómez, María Adelaida (bioRxiv, 2020)
SYNOPSIS Background Host cell functions that participate in the pharmacokinetics and pharmacodynamics (PK/PD) of pentavalent antimonials for treatment of American cutaneous leishmaniasis (CL) are critical for drug efficacy. Objectives In this study, we investigated whether macrophage mechanisms of xenobiotic detoxification contribute to drug-dependent elimination of intracellular Leishmania. Methods Transcriptomes of primary macrophages from CL patients (n=6), exposed ex vivo to Leishmania infection and SbV were generated. Candidate genes were selected and validated using short harping RNA interference (shRNA) in THP-1 cells. Results Strong induction of metallothionein (MT) genes was observed upon Leishmania infection and exposure to SbV, with 7 MT genes (MT1 and MT2 family members) appearing within the top 20 up-regulated genes. Tandem knockdown (KD) of MT2-A and MT1-E, 1F, and 1X in THP-1 cells was achieved using a pan-MT shRNA., Intracellular parasite survival after SbV exposure was unaffected in tandem-KD cells, and this was a consequence of strong transcriptional upregulation of MTs by infection and SbV, overcoming the KD effect. Gene silencing of the metal transcription factor-1 (MTF-1) abrogated expression of MT1 and MT2-A genes. Upon exposure to SbV, intracellular survival of Leishmania in MTF-1KD cells was significantly enhanced (p ≤ 0.05). Conclusions MTs are potent scavengers of heavy metals, and central elements of the mammalian cell machinery for xenobiotic detoxification. Results from this study highlight the participation of macrophage MTs in Sb-dependent parasite killing, revealing novel strategies for host-targeted optimization of antileishmanial drugs. Competing Interest Statement The authors have declared no competing interest.